Insight into the uptake, accumulation, and metabolism of the fungicide phenamacril in lettuce (Lactuca sativa L.) and radish (Raphanus sativus L.). (1st July 2022) - Tao, Yan; Xing, Yinghui; Jing, Junjie; Yu, Pingzhong; He, Min; Zhang, Jinwei; Chen, Li; Jia, Chunhong; Zhao, Ercheng
Abstract: The fungal species Fusarium can cause devastating disease in agricultural crops. Phenamacril is an extremely specific cyanoacrylate fungicide and a strobilurine analog that has excellent efficacy against Fusarium. To date, information on the mechanisms involved in the uptake, accumulation, and metabolism of phenamacril in plants is scarce. In this study, lettuce and radish were chosen as model plants for a comparative analysis of the absorption, accumulation, and metabolic characteristics of phenamacril from a polluted environment. We determined the total amount of phenamacril in the plant-water system by measuring the concentrations in the solution and plant tissues at frequent intervals over the exposure period. Phenamacril was readily taken up by the plant roots with average root concentration factor ranges of 60.8–172.7 and 16.4–26.9 mL/g for lettuce and radish, respectively. However, it showed limited root-to-shoot translocation. The lettuce roots had a 2.8–12.4-fold higher phenamacril content than the shoots; whereas the radish plants demonstrated the opposite, with the shoots having 1.5 to 10.0 times more phenamacril than the roots. By the end of the exposure period, the mass losses from the plant-water systems reached 72.0% and 66.3% for phenamacril in lettuce and radish, respectively, suggesting evidence of phenamacril biotransformation. Further analysis confirmed that phenamacril was metabolized via hydroxylation, hydrolysis of esters, demethylation, and desaturation reactions, and formed multiple transformation products. This study furthers our understanding of the fate of phenamacril when it passes from the environment to plants and provides an important reference for its scientific use and risk assessment. Graphical abstract: Image 1 Highlights: Lettuce and radish were capable of absorbing phenamacril by roots. Phenamacril showed limited root-to-shoot translocation in lettuce plants. Phenamacril had a 1.5–10.0-fold higher content in radish shoots than the roots. Phenamacril was metabolized to multiple transformation products within plants.